Desempenho do girassol em diferentes épocas de semeadura na região noroeste do Rio Grande do Sul. - Cadorin, Antonio Mauro Rodrigues (2010)
The production of sunflower (Helianthus annuus L.) in Brazil is booming, in emphasis there is the south with an acreage of 17% with the oilseed. The performance of sunflower is directly related to the choice about many factors like sowing date, genotype, the appropriate management and soil fertility, crop rotation, crop succession and especially environmental factors. This culture adapts to different soil and edaphoclimatic conditions and can be cultivated in almost all over Brazil. On this basis, the aim of this work was to evaluate the cultivation environment influence and sowing date on phonology and morphology traits of sunflower. Besides identifying the main stages of culture development within sowing dates tested. It also aimed to build a model based on multiple linear regression equations that express the growth of sunflower under field conditions. And this way can be used as a tool to estimate the potential yield of sunflower to the Northwestern of RS, based on the projection of meteorological variables for the period and management since the establishment to harvest this important oilseed. For this, was evaluated the genotypes Hélio 250, 251, 358, 884 and 885 in the 2008-09 harvest and genotypes Hélio 250, 251, 253, 360, 211, and HLA 211, and Paraíso 33 in the 2009-10 harvest in three seasons (August, October and December). The experiment was conducted in Random Block Complete with four replications on the UFSM Campus in Frederico Westphalen, in Northwestern Brazil. The morphological traits measured were plant height, chapter size, a thousand seeds weight and yield. Phenological characters were days of sowing emergence (S-E), days from emergence to early flowering (E-FI) days from initial flowering to full flowering (FI-FP) and days of full flowering to physiological maturity (FP-MF). Individual analysis and combined and the averages compared by Tukey test at 5% were realized. The models estimated form multiple linear regression equations, using, the method Backward in the 5% level of error probability. The independent variables in models of entry were: TM, Tmin, Tmax, PP and GD of each phonologic stage. The phonologic stage and yield were the dependent variables. Based on results, concludes that the morphological traits plant height, is influenced by the environment and sowing dates, for the chapter size there is the environment influence and was found that the yield has positively answers to environmental conditions and sowing times. For the studied phonological traits also occurs influence of environmental conditions and sowing date. With the exception onset flowering to full flowering witch presents no interference form the sowing time. When evaluated the agrometeorological variables interference, we can say that there was no interaction between them and the dependent variables, it can be said that the thermal plus and the maximum and minimum temperatures are crucial for the phonological sub-stages of sunflower, been the achene yield influenced just for the thermal plus for the sub-stages form sowing to emergence and since this with the initial flowering and full flowering. About the sowing stages, the August present an increase of the plant cycle, while in the December suggests a cycle reduction, and that the sowing in October is the culture preferred phase to Northwestern region of the RS.